KIPRAH DAN KONTRIBUSI JAMALUDDIN Al-AFGHANI DALAM PEMIKIRAN MODERN ISLAM - Dwi Sukmanila (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2019)
Jamaluddin al-Afghani as an Islamic warrior figure gave a lot of time in his life as an Islamic service and struggle as long as it was elaborated in the discussion above. in fighting he is uncompromising of the injustice and authoritarian nature of a government. This is a distinctive characteristic of his character who is firm in upholding the truth. His struggle inside was extraordinary, it was seen with his long-running actions in various countries to save Islam from the trap of materialism to divide Muslims. thus, Afghani and Pan Islamism tried to reunite Muslims worldwide, and open the horizons of Islamic societies to be able to live independently without expecting assistance from the West, in various aspects so that there was no dependence between Muslims and the West.